2010
DOI: 10.3109/07435801003769995
|View full text |Cite
|
Sign up to set email alerts
|

Central Administration of Kisspeptin-10 Inhibits Water and Sodium Excretion of Anesthetized Male Rats and the Involvement of Arginine Vasopressin

Abstract: Central administration of kisspeptin-10 could inhibit sodium excretion and urine flow in anesthetized male rats, which is probably mediated by increasing the plasma AVP concentration and is independent of plasma ANP concentration and renal sympathetic nerve activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…; Ten et al . ), and to increase mEPSC frequency in vasopressin neurones in brain slices from male rats (Yokoyama et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Ten et al . ), and to increase mEPSC frequency in vasopressin neurones in brain slices from male rats (Yokoyama et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…I.C.V. kisspeptin has been shown to increase plasma vasopressin concentrations in male rats (Han et al 2010;Ten et al 2010), and to increase mEPSC frequency in vasopressin neurones in brain slices from male rats (Yokoyama et al 2014). While this might represent a sex difference in the regulation of vasopressin neurones by kisspeptin, it is possible that paraventricular nucleus vasopressin neurones respond differently than supraoptic nucleus oxytocin neurones to I.C.V.…”
Section: Effects Of Kisspeptin On Vasopressin Neuronesmentioning
confidence: 99%
“…A recent study demonstrated that icv kisspeptin-10 increases plasma vasopressin after 30 min, with a concurrent decrease in sodium excretion and urine production (17). These observations are most easily be explained by increased vasopressin secretion, which would be expected to result from an increased firing rate of vasopressin neurons.…”
Section: Figmentioning
confidence: 96%
“…Previous studies have shown that iv administration of kisspeptin-10 to female rats increases plasma oxytocin levels (5), whereas intracerebroventricular (icv) injection of kisspeptin-10 to male rats increases plasma vasopressin concentrations (17). To date, there are no reports of the effects of icv kisspeptin on oxytocin levels or of iv kisspeptin on vasopressin levels.…”
mentioning
confidence: 97%
“…Central administration of KP-10 also inhibits sodium excretion and the urine flow, presumably by increasing the plasma vasopressine concentration [30].…”
Section: Discussionmentioning
confidence: 99%